Computer Methods and Programs in Biomedical Signal and Image Processing - Wang, Lulu (IntechOpen, 2020)
This book aims to provide a brief update to the current status of and advances in computational methods and programs used for the development of the theory and practice of biomedical signal and image communication. The book comprises a collection of invited manuscripts, written in a convenient way and of manageable length. These timely collections will provide an invaluable resource for initial inquiries into technologies and will encapsulate the latest developments and applications with reference sources for further detailed information. The methods described in this book cover a wide range of computational algorithms that are widely used in bioengineering and biomedicine. The content and format are specifically designed to stimulate the further development and application of these technologies by reaching out to non-specialists across a broad audience. This book is intended to expose the latest developments of scientists and engineers covering a variety of complementary topics, to enhance people's overall understanding of computer science and biomedical image communications. It will benefit students, scientists, and researchers in applied computer science. Engineers and clinicians working in imaging will also find this book useful.